Analytical expression for the current-voltage characteristics of organic bulk heterojunction solar cells - Inche Ibrahim, Mohd Lukman; Ahmad, Zubair; Sulaiman, Khaulah (American Institute of Physics, 2015)
An expression to describe the current-voltage characteristics of organic bulk heterojunction (BHJ) solar cells is derived. The derivation is obtained by analytically solving the drift-diffusion model for organic BHJ solar cells with the assumption of uniform bimolecular recombination rate. The assumption of uniform bimolecular recombination rate leads to somewhat inaccurate, for example, carrier densities as functions of the position inside the device. However, we show that this assumption should still produce an expression for the current as a function of applied voltage as if the actual bimolecular recombination rate is considered in the derivation. Applying this analytical expression to experimental current-voltage data enable us to directly extract and analyze, for example, the recombination loss of an organic BHJ solar cell as a function of applied voltage.